Metal-graphene interfaces in epitaxial and bulk systems: A review. (May 2020) - Yang, Ming; Liu, Yue; Fan, Tongxiang; Zhang, Di
Graphical abstract: Abstract: The prosperity of graphene in the past decade has provided us with both a versatile platform for scientific studies and a multitude of solutions for technological applications. Interfacing graphene with bulk metals is fundamental for a wide range of interesting multi-dimensional systems ranging from incorporating graphene into fully dense metal matrices, and graphene epitaxy on metal substrates to the deposition of metal overlayers on graphene. The microstructure, interaction and properties of metal-graphene interfaces (MGI s), which substantially govern the epitaxial growth mode, mass exchange and overall properties, are central topics for all these metal-graphene systems. This review covers MGIs produced by both bottom-up and top-down approaches, which correspond to epitaxial and bulk metal-graphene systems, respectively. Importantly, we attempt to link and build a bridge among these systems, with highlight on the shared roles and critical functions of MGIs. We describe the structure, physicochemcial properties, fabrication and optimum design of MGIs, and we examine the roles of their properties and pertinent phenomena in governing the overall performance in a vast array of specific applications. We conclude by making a prospect on MGIs and underscoring the concept of interface nanoengineering for a broad spectrum of metal/low-dimensional material hybrid systems.